Infection Spread, Recovery, and Fatality from Coronavirus in Different Provinces of Saudi Arabia - Mohammed Muberek Alharbi (Healthcare, 2021)
The World Health Organization (WHO) announced COVID-19, a novel coronavirus outbreak, as a pandemic in 2020. In the month of February 2020, the disease began to spread through the Middle East. The first case of COVID-19 in the Kingdom of Saudi Arabia was identified in March 2020, and it is now one of the region’s most affected countries. Analyzing the disease’s propagation pattern may aid in the development of pandemic-fighting strategies. This study aims to analyze the trend of COVID-19’s spread, its recovery, and mortality in the Kingdom of Saudi Arabia (KSA). Two to three major cities from the 13 provinces of the country were chosen, and the rate of infection recovery was recorded from the first month until the number of confirmed cases showed a decline. The data published on the official Ministry of Health website were recorded on an Excel sheet, graphically represented as figures to indicate the pattern of spread. According to the study’s findings, COVID-19 positive cases were discovered in the majority of provinces as early as March 2020. The province of Makkah had the largest number of COVID-19 positive cases (30.7%), followed by Riyadh (23%). The province of Al Jowf had the lowest number of COVID-19 cases (0.3%). Tabuk province had the highest rate of recovery (97.8%), followed by the Northern Border Province (96.7%). Makkah province had the highest mortality rate (2.6%), followed by Al Jawf province (2.4%). The peak case–fatality ratio was recorded in August and September. The highest number of tests to detect the COVID-19 was performed in the month of July, and the highest percentage of positive cases was detected in June (19.55%). All the provinces from the month of September 2020 showed a progressive decline in the number of confirmed COVID-19 cases. According to this study, COVID-19 infection was found in the majority of Saudi Arabian provinces in March 2020, with a peak in June–July 2020. Considering the climatic and demographic characteristics of the region, specific modalities need to be adopted in collaboration with international guidelines to defeat the COVID-19 pandemic.